Keteladanan Profetik dalam Al-Qur’an dan Hadis sebagai Basis Pendidikan Agama Islam Abad Ke-21 - Kamarudin Zaelani; Fathurrahman Fathurrahman (Alpatih Harapan Semesta, 2026)
This study examines the portrayal of the 25 prophets and messengers along with their prayers in the Qur’an and Hadith and their relevance to Islamic Religious Education (PAI) in the 21st century. The research employed a qualitative approach using library research methods through the analysis of primary and secondary sources, including the Qur’an, Hadith, tafsir books, books, and scientific articles. The findings reveal that the stories and prayers of the prophets contain exemplary values of spirituality, morality, leadership, patience, and responsibility that are highly relevant to the challenges of modern education. These values can strengthen Islamic Religious Education in shaping religious, moderate, humanistic, and adaptive character in response to technological advancement and social change. Furthermore, the stories and prayers of the prophets can serve as contextual learning media to develop students’ spiritual awareness and ethical values in the digital era. Therefore, the integration of prophetic values into Islamic Religious Education plays an important role in addressing the moral and spiritual crises of 21st-century society.